Estudio comparativo bromatológico y microbiológico de la leche cruda y pasteurizada de consumo humano en la ciudad de Santa Rosa El Oro. - Zambrano Moscoso, Lina G. (2008)
In Santa Rosa s city, I carried out the present field investigation in the I study comparative bromatologist and microbiologist of the raw and pasteurized milk of human consumption, for that which I took six samples to milk, the most representative as for their daily demand in this population three samples of parteusized (the milkmaind, nuturimilk and the little ranch) and three raw samples of milk of sale free to the bulk.